Chronic stress-associated visceral hyperalgesia correlates with severity of intestinal barrier dysfunction. Issue 9 (September 2018) - Creekmore, Amy L.; Hong, Shuangsong; Zhu, Shengtao; Xue, Jing; Wiley, John W.
Abstract : Abstract: In humans, chronic psychological stress is associated with increased intestinal paracellular permeability and visceral hyperalgesia, which is recapitulated in the chronic intermittent water avoidance stress (WAS) rat model. However, it is unknown whether enhanced visceral pain and permeability are intrinsically linked and correlate. Treatment of rats with lubiprostone during WAS significantly reduced WAS-induced changes in intestinal epithelial paracellular permeability and visceral hyperalgesia in a subpopulation of rats. Lubiprostone also prevented WAS-induced decreases in the epithelial tight junction protein, occludin (Ocln). To address the question of whether the magnitude of visceral pain correlates with the extent of altered intestinal permeability, we measured both end points in the same animal because of well-described individual differences in pain response. Our studies demonstrate that visceral pain and increased colon permeability positively correlate (0.6008, P = 0.0084). Finally, exposure of the distal colon in control animals to Ocln siRNA in vivo revealed that knockdown of Ocln protein inversely correlated with increased paracellular permeability and enhanced visceral pain similar to the levels observed in WAS-responsive rats. These data support that Ocln plays a potentially significant role in the development of stress-induced increased colon permeability. We believe this is the first demonstration that the level of chronic stress-associated visceral hyperalgesia directly correlates with the magnitude of altered colon epithelial paracellular permeability. Abstract : These studies show the magnitude of visceral hyperalgesia correlates with the level of colon epithelial permeability dysfunction in a water avoidance stress rat model.